Bioversity International Annual Report 2012 - Bioversity International (Bioversity International, 2013)
Throughout Bioversity International’s 2012 Annual Report you will find highlights of our work in 2012 showing how research on agricultural and forest biodiversity can help achieve a sustainable future. The report gives examples of how our work contributes to ten CGIAR Research Programs, information about Bioversity’s participation in key events that marked 2012 and some highlights of our research products. In the report, which is also available as an interactive digital publication, you will also find a list of our research partners and funding partners in 2012.